Proceedings of the 5th International Conference on Predictor Models in Software Engineering 2009
DOI: 10.1145/1540438.1540442
|View full text |Cite
|
Sign up to set email alerts
|

Can we build software faster and better and cheaper?

Abstract: "Faster, Better, Cheaper" (FBC) was a development philosophy adopted by the NASA administration in the mid to late 1990s. that lead to some some dramatic successes such as Mars Pathfinder as well as a number highly publicized mission failures, such as the Mars Climate Orbiter & Polar Lander.The general consensus on FBC was "Faster, Better, Cheaper? Pick any two". According to that view, is impossibly to optimize on all three criteria without compromising the third. This paper checks that view using an AI searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…SEESAW is a variant of MaxWalkSat we first reported in [12]. While searching the ranges of a feature, this algorithm exploits the monotonic nature of Equation 5 and Equation 6.…”
Section: A Alternate Search Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…SEESAW is a variant of MaxWalkSat we first reported in [12]. While searching the ranges of a feature, this algorithm exploits the monotonic nature of Equation 5 and Equation 6.…”
Section: A Alternate Search Methodsmentioning
confidence: 99%
“…Fortunately, we have found that the USC COCOMO and COQUALMO models [38] are "just right". In all our studies [8]- [12] we have found that prediction variance can be controlled by only constraining project options while letting the tuning variance remaining unchecked. Hence, we use these models for our research.…”
Section: Dodging Tuning Variancementioning
confidence: 99%
See 2 more Smart Citations
“…SEESAW was first introduced in [18] and has been applied to numerous domains [10,16,17,[20][21][22]. W was first introduced in [8] but that report includes no comparisons with other quality optimizers.…”
Section: Introductionmentioning
confidence: 99%